Comparison of Government’s Strategic Aims and Company Needs within the Hungarian Startup Ecosystem - Szakos, Judit (European Scientific Journal, ESJ, 2022)
Startup companies are frequently perceived by the host state to be important actors who are increasing the economic competitiveness of the state’s economy and its wider region. In response, states usually design assistance strategies to increase these startups’ effectiveness. But credibly measuring whether these assistance strategies meet their stated goals is problematic, as there is a dearth/lack of suitable information related to startups to make the needed assessments. This paper aims to compare what Hungarian startup companies were struggling with and whether the Hungarian state’s central entrepreneurial and innovation strategies intended to assist these startups were actually in alignment. The paper derives its data from the Hungarian Startup Report, the latest report from the Global Entrepreneurship Monitor, and relevant government strategies and uses content analysis to make its comparisons. The findings are categorized using Ben Spiegel’s entrepreneurial attributes-based ecosystem model. Overall, the paper finds that many of the needs of the startups were addressed in government strategies at the abstract level on the cultural attribute side, but social and material attributes have mismatches and needed to be covered. This raises future questions on the effectiveness of the Hungarian government’s startup assistance strategy and its implementation.